LDH-PFA composite anti-corrosion powder coating, coating and preparation method
By adding layered bimetallic hydroxide (LDH) to the PFA coating, the LDH-PFA composite anticorrosion coating is prepared, which solves the problem that the PFA coating is prone to pores after baking at high temperatures, and significantly improves the corrosion resistance and corrosion resistance.
Patent Information
- Application Number
- CN202411960800.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
The existing PFA anticorrosion coating is prone to pores after baking at high temperature, resulting in coating failure and unable to effectively prevent corrosion.
Laminated bimetallic hydroxide (LDH) is added to the PFA coating, and LDH-PFA composite anticorrosion powder coating is prepared by co-precipitation method or hydrothermal method. After spraying on the surface of the substrate, it is cured to form an LDH-PFA composite anticorrosion coating.
The LDH-PFA composite anti-corrosion coating significantly improves corrosion resistance, enhances the barrier properties and corrosion resistance of the coating, can effectively prevent corrosive media from penetration, and extends the service life of the substrate.
Smart Images

Figure CN119708933A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-corrosion coatings, and in particular to a LDH-PFA composite anti-corrosion powder coating, a coating and a preparation method thereof. Background Art
[0002] With the rapid development of society, various alloys are widely used in various fields due to their excellent mechanical properties. The performance and service life of alloys can be affected by corrosion problems and cause safety hazards, which is particularly important in key industries such as aviation, construction and transportation. Therefore, the development and implementation of effective anti-corrosion strategies has become a key task in the field of materials science.
[0003] Soluble polytetrafluoroethylene (PFA, also known as perfluoroalkoxyalkane) has excellent chemical and thermal stability and is widely used in the field of alloy corrosion protection. In the molecular structure of PFA, the electronegativity of fluorine atoms is relatively large, resulting in repulsion between adjacent fluorine atoms, which leads to a helical arrangement of the molecular structure. However, this unique configuration is prone to form obvious pores in the high-temperature molten state, so after high-temperature baking to form a film, there will be defective sites in the resulting coating, which allow corrosive media to penetrate the coating, eventually leading to coating failure. Summary of the invention
[0004] In view of this, the present invention provides a LDH-PFA composite anti-corrosion powder coating, a coating and a preparation method thereof. In the present invention, layered double metal hydroxide is added to the PFA coating, which can greatly improve the anti-corrosion performance of the coating.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] A LDH-PFA composite anticorrosive powder coating comprises layered double metal hydroxide powder and soluble polytetrafluoroethylene powder; the mass of the layered double metal hydroxide powder is 1-1.2% of the mass of the soluble polytetrafluoroethylene powder.
[0007] Preferably, the divalent metal ion in the layered double hydroxide powder is Mg 2+ 、Zn 2+ and Ni 2+ One or more of the trivalent metal ion is Al 3+ and Co 3+ One or two of the following: the molar ratio of divalent metal ions to trivalent metal ions in the layered double hydroxide powder is 1.5 to 3:1;
[0008] The interlayer anion of the layered double hydroxide powder is VO3 - 、CO3 2- or NO3 -.
[0009] Preferably, the layered double hydroxide powder has an interlayer anion of VO3 - The zinc-aluminum layered double hydroxide and the interlayer anion is CO3 2- One or two of the magnesium-aluminum layered double hydroxides.
[0010] The present invention also provides a method for preparing the LDH-PFA composite anticorrosive powder coating of the above scheme, comprising the following steps: mixing layered double metal hydroxide powder and soluble polytetrafluoroethylene powder in an alcohol solvent and then drying to obtain the LDH-PFA composite anticorrosive powder coating.
[0011] Preferably, the preparation method of the layered double hydroxide powder is a coprecipitation method or a hydrothermal method.
[0012] The present invention also provides a LDH-PFA composite anti-corrosion coating, which is formed by the LDH-PFA composite anti-corrosion powder coating described in the above scheme or the LDH-PFA composite anti-corrosion powder coating prepared by the preparation method described in the above scheme.
[0013] Preferably, the method comprises the following steps: spraying the LDH-PFA composite anti-corrosion powder coating on the surface of a substrate and then curing the coating to obtain the LDH-PFA composite anti-corrosion coating.
[0014] Preferably, the substrate is a metal substrate.
[0015] Preferably, the spraying is electrostatic spraying; the conditions of the electrostatic spraying include: voltage of 55-65KV, current of 95-100UA, and spraying distance of 15-25cm.
[0016] Preferably, the curing temperature is 360-365° C., the heat preservation time is 1-1.5 h, and the heating rate to the curing temperature is 3.5-4° C. / min.
[0017] The present invention provides a LDH-PFA composite anticorrosive powder coating, comprising layered double hydroxide powder and soluble polytetrafluoroethylene powder; the mass of the layered double hydroxide powder is 1 to 1.2% of the mass of the soluble polytetrafluoroethylene powder. Layered double hydroxide (LDH) is a two-dimensional nanomaterial with a unique two-dimensional layered structure and a large aspect ratio, which can effectively extend the path for corrosive substances to enter the substrate, and at the same time can improve the barrier property of the coating, avoid the appearance of pores in the coating after baking and film formation, thereby greatly enhancing the corrosion resistance of the coating; in addition, LDH exhibits excellent anion exchange capacity, enabling it to adsorb corrosive ions, reduce the contact between the corrosive ions and the substrate, and thus avoid corrosion of the substrate.
[0018] Furthermore, the LDH used in the present invention can be a layer with an interlayer anion of VO3 - Zinc-aluminum layered double hydroxide (LDH(VO3 - )) and the interlayer anion is CO3 2- Magnesium aluminum layered double hydroxide (LDH(CO3 2- )) one or two of which LDH(VO3 - ) contains VO3 - , VO3 - It is a corrosion inhibitor ion that can effectively slow down or prevent the chemical or electrochemical reaction of metals in corrosive environments, further improving the anti-corrosion performance of the coating. The results of the embodiment show that the impedance of pure PFA coating to chloride ions is 1.12×10 3 Ω·cm 2 , and the addition of LDH(CO3 2- ) and LDH(VO3 - ) after the coating's impedance to chloride ions increased to 1.04×10 4 Ω·cm 2 and 2.1×10 5 Ω·cm 2 , the anti-corrosion performance has been significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 LDH (VO3 prepared in Example 1 - ) powder and LDH (CO3 prepared in Example 2 2- ) XRD pattern of powder;
[0020] Figure 2 LDH (VO3 prepared in Example 1 - ) IR pattern of powder;
[0021] Figure 3 LDH (VO3 prepared in Example 1 - ) SEM image of powder;
[0022] Figure 4 LDH (CO3 prepared in Example 2 2- ) / PFA composite coating cross section SEM image;
[0023] Figure 5 The SEM image of the cross section of the PFA coating prepared in Comparative Example 1;
[0024] Figure 6 The EIS impedance spectra of the coatings prepared in Examples 1 to 2 and Comparative Example 1, wherein the left side is the impedance Nyquist diagram, the middle is the impedance Bode mode diagram, and the right side is the impedance Bode phase diagram;
[0025] Figure 7 LDH (CO3 prepared in Comparative Example 2 2- ) / PFA composite coating photos;
[0026] Figure 8 LDH (CO3 prepared in Example 2 2- ) / PFA composite coating. DETAILED DESCRIPTION
[0027] The invention provides a LDH-PFA composite anticorrosive powder coating, which comprises layered double metal hydroxide powder and soluble polytetrafluoroethylene powder; the mass of the layered double metal hydroxide powder is 1-1.2% of the mass of the soluble polytetrafluoroethylene powder.
[0028] In the present invention, the divalent metal ions in the layered double hydroxide powder are preferably Mg 2+ 、Zn 2+ and Ni 2+ One or more of, more preferably Mg 2+ or Zn 2+ The trivalent metal ion in the layered double hydroxide powder is preferably Al 3+ and Co 3+ One or two of the following, more preferably Al 3+ ; The molar ratio of divalent metal ions to trivalent metal ions in the layered double hydroxide powder is preferably 1.5 to 3:1, more preferably 2:1.
[0029] In the present invention, the interlayer anion of the layered double hydroxide powder is VO3 - 、CO3 2- or NO3 - , more preferably VO3 - or CO3 2- , more preferably VO3 - In the present invention, VO3 - It is a corrosion inhibitor ion that can effectively slow down or prevent the chemical or electrochemical reaction of metals in corrosive environments, further improving the anti-corrosion performance of the coating.
[0030] In the present invention, the layered double hydroxide powder is preferably a layered double hydroxide powder having an interlayer anion of VO3 - Zinc-aluminum layered double hydroxide (LDH(VO3 - )) and the interlayer anion is CO3 2- The magnesium aluminum layered double hydroxide (LDH(CO3 2- ))One or both.
[0031] In the present invention, the layered double hydroxide powder is specifically a layered double hydroxide nanosheet, and the size of the layered double hydroxide nanosheet is preferably 1 to 2 μm. Specifically, the LDH (CO3 2- ) has a size of 1.5 to 2 μm, and the LDH (VO3 - ) size is 1 μm.
[0032] In the present invention, the mass of the layered double hydroxide powder is 1-1.2% of the mass of the soluble polytetrafluoroethylene powder, preferably 1%. The present invention controls the amount of the layered double hydroxide powder within the above range, which not only ensures the excellent physical and chemical properties of PFA, but also enhances the corrosion resistance of PFA. Too much addition will make the surface of the PFA material porous, the material becomes very brittle, and the toughness is greatly reduced.
[0033] The present invention also provides a method for preparing the LDH-PFA composite anticorrosive powder coating of the above scheme, comprising the following steps: mixing layered double metal hydroxide powder and soluble polytetrafluoroethylene powder in an alcohol solvent and then drying to obtain the LDH-PFA composite anticorrosive powder coating.
[0034] In the present invention, the preparation method of the layered double hydroxide powder is a coprecipitation method or a hydrothermal method. Specifically, when the layered double hydroxide powder is LDH (VO3 - ), preferably prepared by coprecipitation; the coprecipitation method is used to prepare LDH (VO3 - ) preferably comprises: dissolving zinc salt and aluminum salt in water to obtain a mixed metal salt solution; simultaneously dropping the mixed metal salt solution and sodium hydroxide solution into a saturated NaVO3 solution to perform a coprecipitation reaction to obtain the LDH (VO3 -); the zinc salt is preferably zinc nitrate, specifically Zn(NO3)2·6H2O, and the aluminum salt is preferably aluminum nitrate, specifically Al(NO3)3·9H2O; the molar ratio of the zinc salt to the aluminum salt is preferably 2:1; the total concentration of the zinc salt and the aluminum salt in the mixed metal salt solution is preferably 0.5-0.7 mol / L, more preferably 0.6 mol / L; the concentration of the sodium hydroxide solution is preferably 1.5-2.5 mol / L, more preferably 2 mol / L; the volume ratio of the mixed metal salt solution, the sodium hydroxide solution and the saturated NaVO3 solution is preferably 10:10:7-8, more preferably 10:10:7.5; the pH value of the system is preferably controlled to be 9-10 during the dropwise addition process; the temperature of the coprecipitation reaction is preferably 55-65°C, more preferably 60°C, and the reaction time is preferably 23-25h, more preferably 24h. The coprecipitation reaction time is counted from the completion of the dropwise addition of the mixed metal salt solution and the sodium hydroxide solution; the coprecipitation reaction is preferably carried out under stirring; the dropwise addition and reaction process is preferably carried out under nitrogen protection; after the coprecipitation reaction is completed, the obtained product is washed and dried to obtain the LDH (VO3 - The present invention is prepared under the above conditions to obtain LDH (VO3 - ) nanosheets.
[0035] In the present invention, when the layered double hydroxide powder is LDH(CO3 2- ), preferably a hydrothermal method is used for preparation; the hydrothermal method for preparing LDH (CO3 2- The step of ) preferably comprises: mixing magnesium salt, aluminum salt, urea and water for hydrothermal reaction to obtain the LDH (CO3 2- ); the magnesium salt is preferably magnesium nitrate, specifically Mg(NO3)2·6H2O, the aluminum salt is preferably aluminum nitrate, specifically Al(NO3)3·9H2O; the molar ratio of the magnesium salt, aluminum salt and urea is preferably 2:1:4.5-5.5, more preferably 2:1:5; the temperature of the hydrothermal reaction is preferably 100-120°C, more preferably 110°C, and the time of the hydrothermal reaction is preferably 20-30h, more preferably 24h. After the hydrothermal reaction is completed, the obtained product is washed and dried to obtain the LDH(CO3 2- ). The present invention is prepared under the above conditions to obtain LDH (CO3) with uniform size. 2- ) nanosheets.
[0036] In the present invention, the alcohol solvent is preferably ethanol; the mixing is preferably stirring mixing, and the stirring mixing time is preferably 10 to 15 hours, more preferably 12 hours; in a specific embodiment of the present invention, the layered double hydroxide powder and the soluble polytetrafluoroethylene powder are preferably added to the alcohol solvent, and then stirred and mixed, and then dried after the stirring and mixing is completed; the drying temperature is preferably 60°C, and the drying time is preferably 12 hours.
[0037] The present invention also provides a LDH-PFA composite anticorrosion coating, which is formed by the LDH-PFA composite anticorrosion powder coating described in the above scheme or the LDH-PFA composite anticorrosion powder coating prepared by the preparation method described in the above scheme. In the present invention, the thickness of the LDH-PFA composite anticorrosion coating is preferably 50 to 70 μm.
[0038] The present invention also provides a method for preparing the LDH-PFA composite anti-corrosion coating of the above scheme, comprising the following steps: spraying the LDH-PFA composite anti-corrosion powder coating on the surface of a substrate and then curing it to obtain the LDH-PFA composite anti-corrosion coating.
[0039] In the present invention, the substrate is a metal substrate, and the metal substrate can be an alloy, such as a magnesium alloy. In a specific embodiment of the present invention, the substrate is preferably polished to a smooth surface and then placed in ethanol for ultrasonic treatment to remove residual grease on the surface, and then sprayed; the polishing is preferably performed using 240#, 800#, 1000#, 1500#, and 2000# sandpaper in sequence.
[0040] In the present invention, the spraying is preferably electrostatic spraying; the conditions of the electrostatic spraying preferably include: voltage of 55-65KV, preferably 61KV, current of 95-100UA, preferably 98UA, and spraying distance of 15-25cm, preferably 20cm. The present invention adopts electrostatic spraying technology to prepare the coating, the operation process is simple, and it has the potential to achieve large-scale industrial application.
[0041] In the present invention, the curing temperature is preferably 360-365°C, more preferably 360°C, the holding time is preferably 1-1.5h, more preferably 1h, the heating rate to the curing temperature is preferably 3.5-4°C / min, more preferably 4°C / min; the curing is preferably carried out in a muffle furnace. The present invention can obtain an anti-corrosion coating with excellent performance by curing under the above conditions.
[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Example 1
[0044] LDH(VO3 - ) / PFA composite coating preparation method, the specific preparation steps are as follows:
[0045] Preparation of LDH(VO3 - ): Dissolve 11.90g Zn(NO3)2·6H2O and 7.50g Al(NO3)3·9H2O in 100mL deionized water (boil and cool) to obtain a nitrate mixed solution with a total concentration of 0.6mol / L. Weigh 8g NaOH to prepare 100mL NaOH solution with a concentration of 2mol / L. Transfer the nitrate mixed solution and NaOH solution to a constant pressure dropping funnel respectively. Prepare 75mL NaVO3 saturated solution and transfer it to a four-necked flask. Slowly add the nitrate mixed solution and sodium hydroxide solution to the NaVO3 saturated solution. During the addition, maintain the system pH between 9 and 10 until the nitrate mixed solution is added. Then, keep it warm and stir for 24h at 60℃. Use nitrogen protection during the addition and the stirring process. After the reaction is completed, wash it three times with deionized water and once with ethanol water until the supernatant is colorless. Dry it in a vacuum at 60℃ for 24h to obtain LDH(VO3 - )powder.
[0046] Weigh 25g PFA and 0.25g LDH(VO3 - ) powder, mix the two powders in 200 mL of ethanol, stir for 12 h to ensure full mixing. Transfer to a 6 ° C oven and dry for 12 h to obtain LDH (VO3 - ) / PFA composite anti-corrosion powder coating.
[0047] The alloy plate was polished with 240#, 800#, 1000#, 1500#, and 2000# sandpaper in sequence until the surface was smooth, and then placed in ethanol and ultrasonically removed the residual grease on the surface. Electrostatic spraying equipment was used to spray at a distance of 20 cm from the surface of the alloy plate, with a spraying voltage of 61KV and a current of 98UA. After spraying, it was placed in a muffle furnace and heated to 360°C at a rate of 4°C / min and maintained for 1 hour to obtain LDH (VO3 - ) / PFA composite coating.
[0048] Example 2
[0049] LDH(CO3 2- ) / PFA composite coating preparation method, the specific preparation steps are as follows:
[0050] Preparation of LDH(CO3 2- ): 6.14 g Mg(NO3)2·6H2O, 4.512 g Al(NO3)3·9H2O, and 7.2 g urea were dissolved in 200 mL deionized water to obtain a mixed solution. The mixture was transferred to a high-pressure reactor and reacted at 110°C for 24 h. After the reaction was completed, the mixture was washed three times with deionized water and once with ethanol water until the supernatant was colorless. The mixture was dried under vacuum at 60°C for 24 h to obtain LDH(CO3 2- )powder.
[0051] Weigh 25 g PFA and 0.25 g LDH(CO3 2- ) powder, the two powders were mixed in 200 mL of ethanol, stirred for 12 h to ensure full mixing, and transferred to a 6 ° C oven to dry for 12 h to obtain LDH (VO3 - ) / PFA composite anti-corrosion powder coating.
[0052] The alloy plate was polished with 240#, 800#, 1000#, 1500#, and 2000# sandpaper in sequence until the surface was smooth, and then placed in ethanol to remove residual grease on the surface by ultrasonication. Electrostatic spraying equipment was used to spray at a distance of 20 cm from the alloy surface, with a spraying voltage of 61KV and a current of 98UA. After spraying, it was placed in a muffle furnace and heated to 360°C at a rate of 4°C / min and maintained for 1 hour to obtain LDH (CO3 2- ) / PFA composite coating.
[0053] Comparative Example 1
[0054] The preparation method of PFA coating, the specific preparation steps are as follows:
[0055] Weigh 25 g of PFA spray powder. To ensure that the spray powder is in a dry state, transfer the sample to a 60° C. oven and dry it for 12 h to remove moisture.
[0056] The magnesium alloy plate was polished with 240#, 800#, 1000#, 1500#, and 2000# sandpaper in sequence until the surface was smooth, and then placed in ethanol to remove residual grease on the surface by ultrasonic treatment. Electrostatic spraying equipment was used to spray at a distance of 20 cm from the alloy surface, with a spraying voltage of 61KV and a current of 98UA. After spraying, it was placed in a muffle furnace, raised to 360°C at a rate of 4°C / min and maintained for 1h to obtain a PFA coating.
[0057] Characterization and Testing:
[0058] 1. Characterization
[0059] Figure 1 LDH (VO3 prepared in Example 1 - ) powder and LDH (CO3 prepared in Example 2 2- ) XRD pattern of powder, Figure 2 LDH (VO3 prepared in Example 1 - ) IR pattern of powder; according to Figure 1-2 It can be seen that the layered double hydroxides prepared in Example 1 and Example 2 have the target structure.
[0060] Figure 3 LDH (VO3 prepared in Example 1 - ) SEM image of powder. Figure 3 It can be seen that LDH (VO3 - ) The powder is a nanosheet structure with a relatively large aspect ratio.
[0061] Figure 4 is a SEM image of a cross section of the composite coating prepared in Example 2; Figure 5 The SEM image of the cross section of the PFA coating prepared in Comparative Example 1; Figure 4 and Figure 5 It can be seen that the composite coating prepared in Example 2 has layered double metal hydroxide powder distributed ( Figure 4 The coating structure is dense, while the coating in Comparative Example 1 is formed only by PFA, in which no filler is observed; in addition, Figure 5 The thickness of the coating is shown to be relatively small. This is because the edge of the sample was selected when taking the cross-section, so a clearer cross-section can be captured. The actual thickness of the coating in Comparative Example 1 and Example 2 is equivalent, and the addition of LDH does not affect the thickness of the coating.
[0062] 2. Anti-corrosion performance test
[0063] The coatings prepared in Examples 1 to 2 and Comparative Example 1 were placed in an electrochemical workstation (CHI660E, Shanghai Chenhua Instrument Co., Ltd.) for testing. The test conditions were as follows: the test temperature was room temperature, the frequency was 1 Hz to 10 6 Hz, the electrolyte is NaCl solution with a concentration of 3.5wt%, and the coating test area is 1cm 2 The test results show that the impedance of pure PFA coating to chloride ions is 1.12×10 3 Ω·cm 2 , LDH(CO3 2- ) / PFA composite coating has an impedance to chloride ions of 1.04×10 4 Ω·cm 2 , LDH(VO3 -) / PFA composite coating has an impedance of 2.1×10 5 Ω·cm 2 The above results show that adding LDH(CO3 2- ) and LDH(VO3 - ), the anti-corrosion performance of the coating is significantly improved.
[0064] Figure 6 The EIS impedance spectra of the coatings prepared in Examples 1 to 2 and Comparative Example 1 are shown in Figure 1, where the left side is the impedance Nyquist diagram, the middle is the impedance Bode mode diagram, and the right side is the impedance Bode phase diagram. Figure 6 It can be seen that as LDH(CO3 2- ) and LDH(VO3 - ) were added, the impedance arc radius and the intercept value of the impedance modulus showed a significant increase, confirming that LDH (CO3 2- ) and LDH(VO3 - ) has a significant promoting effect on the chloride ion resistance of PFA and can effectively enhance the anti-corrosion ability of the coating.
[0065] Comparative Example 2
[0066] Other conditions were the same as in Example 2, except that LDH(CO3 2- ) powder was added in an amount of 2.5 g (i.e. 10% of the mass of PFA powder); the obtained LDH (CO3 2- ) / PFA composite coating photos Figure 7 As shown in the figure (the composite coating was peeled off from the magnesium alloy plate and then observed), the results showed that holes appeared on the surface of the composite coating, the material became very brittle, the toughness was greatly reduced, and the presence of holes would lead to a decrease in the corrosion resistance of the coating. 2- ) / PFA composite coating photos Figure 8 As shown, it can be seen that the composite coating prepared in Example 2 has no holes on its surface and has good flexibility.
[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A LDH-PFA composite anticorrosive powder coating, characterized in that: The invention comprises layered double metal hydroxide powder and soluble polytetrafluoroethylene powder; the mass of the layered double metal hydroxide powder is 1-1.2% of the mass of the soluble polytetrafluoroethylene powder.
2. The LDH-PFA composite anticorrosive powder coating according to claim 1, characterized in that: The divalent metal ion in the layered double hydroxide powder is Mg 2+ 、Zn 2+ and Ni 2+ One or more of the trivalent metal ion is Al 3+ and Co 3+ One or two of the following: the molar ratio of divalent metal ions to trivalent metal ions in the layered double hydroxide powder is 1.5 to 3:1; The interlayer anions of the layered double hydroxide powder are VO 3- 、CO3 2- or NO 3- .
3. The LDH-PFA composite anticorrosive powder coating according to claim 1, characterized in that: The layered double metal hydroxide powder has an interlayer anion of VO 3- The zinc-aluminum layered double hydroxide and the interlayer anion is CO3 2- One or two of the magnesium-aluminum layered double hydroxides.
4. The method for preparing the LDH-PFA composite anticorrosive powder coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: The layered double metal hydroxide powder and the soluble polytetrafluoroethylene powder are mixed in an alcohol solvent and then dried to obtain the LDH-PFA composite anticorrosive powder coating.
5. The preparation method according to claim 4, characterized in that: The preparation method of the layered double metal hydroxide powder is a coprecipitation method or a hydrothermal method.
6. A LDH-PFA composite anti-corrosion coating, characterized in that: The invention is formed by the LDH-PFA composite anti-corrosion powder coating according to any one of claims 1 to 3 or the LDH-PFA composite anti-corrosion powder coating prepared by the preparation method according to any one of claims 4 to 5.
7. The method for preparing the LDH-PFA composite anticorrosive coating according to claim 6, characterized in that: The following steps are involved: The LDH-PFA composite anti-corrosion powder coating is sprayed on the surface of a substrate and then cured to obtain the LDH-PFA composite anti-corrosion coating.
8. The preparation method according to claim 7, characterized in that: The substrate is a metal substrate.
9. The preparation method according to claim 7, characterized in that: The spraying is electrostatic spraying; the conditions of the electrostatic spraying include: voltage of 55-65KV, current of 95-100UA, and spraying distance of 15-25cm.
10. The preparation method according to claim 7, characterized in that: The curing temperature is 360-365° C., the heat preservation time is 1-1.5 hours, and the heating rate to the curing temperature is 3.5-4° C. / min.
Citation Information
Patent Citations
Electrostatic spraying process for fusible polytetrafluoroethylene anticorrosive coating of chemical equipment
CN112742680A
High-corrosion-resistance fluororesin powder coating composition
CN113604114A
Corrosion-inhibition anion intercalation layered double-metal hydroxide and preparation method and application thereof
CN113716574A
Corrosion-resistant hydrotalcite-like / metal composite coating as well as preparation method and application thereof
CN115110068A
Two powder synthesis of hydrotalcite and hydrotalcite-like compounds with monovalen inorganic anions
US5776424A